Detection of Genes Related to Resistance to Silver Nanoparticles in Bacteria from Secondary Endodontic Infections. (12th September 2019) - Salas-Orozco, Marco Felipe; Martínez, Nereyda Niño; Martínez-Castañón, Gabriel-Alejandro; Méndez, Fernando Torres; Patiño-Marín, Nuria; Ruiz, Facundo
Abstract : Introduction . Silver nanoparticles are used in endodontics due to their antimicrobial activity, although it is considered that bacteria are unable to develop resistance to silver nanoparticles. Silver resistance genes have been related to resistance to nanoparticles and antibiotics. The presence of these resistance genes has not been studied in endodontic bacteria. The objective of this study is to report the prevalence of silver resistance genes in endodontic bacteria. Methods . The selected teeth were isolated using a rubber dam and any restoration, post, or caries was eliminated. The operative field was disinfected, and the root-filling material was removed. The samples were obtained using three sterile paper points to absorb the fluid of the root canal. The DNA from the samples and the control organism was extracted, and the detection of the silCBA resistance genes was carried out by PCR. Results . The results of this study show a high prevalence (73.3%) of silCBA silver resistance genes. The Spearman rank correlation coefficient was utilized to identify correlations between the presence of genes and clinical variables. Conclusions . This study reports a high frequency of silver resistance genes related to nanoparticle resistant from bacteria.